1997
DOI: 10.1046/j.1469-8137.1997.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Fructan metabolism in two species of Bromus subjected to chilling and water stress

Abstract: SUMMARYTwo species of Bromus adapted to different climatic conditions were studied to determine their responses to chilling and water stress. Enzymes of sucrose and fructan metabolism as well as fructoside content were measured in roots and shoots. The results indicate that Bromuspictus (adapted to a cold desert area) has a constitutive fructan synthesis, whilst B. auleticiis (adapted to a warmer northern climate) only accumulated fructan under cold stress. Microscopic observations of roots exposed to fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Fructans have been implicated in protecting plants from cold and water stress and in sustaining sucrose levels in the plant (Pilon‐Smits et al . 1995; Puebla, Salerno & Pontis 1997; Hincha et al . 2002; Konstantinova et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fructans have been implicated in protecting plants from cold and water stress and in sustaining sucrose levels in the plant (Pilon‐Smits et al . 1995; Puebla, Salerno & Pontis 1997; Hincha et al . 2002; Konstantinova et al .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of fructans in the florets at this stage of development has not been reported previously. Fructans have been implicated in protecting plants from cold and water stress and in sustaining sucrose levels in the plant (Pilon-Smits et al 1995;Puebla, Salerno & Pontis 1997;Hincha et al 2002;Konstantinova et al 2002;Pollock et al 2003;Ji et al 2007). Genetic engineering of rice capable of synthesizing fructans has recently been shown to improve chilling tolerance (Kawakami, Sato & Yoshida 2008).…”
Section: Control Of Sink Strength Is Important For Reproductive Stagementioning
confidence: 99%
“…f., a grass species native to a cold arid region with constitutive fructan synthesis showed greater root survival to desiccation than the closely related Bromus auleticus Trin. ex Nees, which accumulates fructan only when exposed to low temperature (Puebla et al, 1997). Although a direct protective role of fructans remains conjectural, the recent demonstration by Demel et al (1998) of a strong and specific interaction between HMW fructans with model membranes suggests that fructans might help prevent lipid condensation and phase transitions to take place in water stress or freeze‐desiccated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Long days (LDs) have been reported to favor accumulation of fructans (Hendry 1987), but this accumulation was probably caused by increased total irradiance in LDs (Solhaug 1991). Fructan synthesis under cold and water stress was compared in two Bromus species adapted to different climatic conditions (Puebla et al 1997). It was found that species adapted to a cold desert climate exhibited constitutive fructan synthesis, whereas species adapted to a warmer climate produced fructans only under cold stress.…”
Section: Introductionmentioning
confidence: 99%